Answer:
Option D
Step-by-step explanation:
A). From the graph attached,
Arrow AB represents the RISE and arrow BC represents the RUN.
B). RUN from point A to B (Horizontal distance) = 2 units
Rise from point A to B (Vertical distance) = -4 [Since, downwards arrow represents negative notation]
Slope of the line segment AB = ![\frac{\text{Rise}}{\text{Run}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7BRise%7D%7D%7B%5Ctext%7BRun%7D%7D)
= ![\frac{-4}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B2%7D)
= -2
Therefore, slope of the line = slope of the line segment AB = -2
Option D will be the correct option.
C=10, C=90°, B=30°, A+B+C=180°
A+30°+90°=180°⇒A=60°
cos30°=a/c
cos30°=a/10⇒a=cos30°*10
a<span>≃8.6602
c²=a²+b²⇒b²=c²-a²
b²=10²-8.6602²⇒b²=25
b=5
</span>
<h3>Given:</h3>
- P= $50,000
- R= 10%
- T= 5 years
<h3>Note that:</h3>
- P= Principal amount
- R= Rate of interest
- T= Time period
<h3>Solution:</h3>
![\large\boxed{Formula: A= P(1+ \frac{R}{100}{)}^{T}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7BFormula%3A%20A%3D%20P%281%2B%20%5Cfrac%7BR%7D%7B100%7D%7B%29%7D%5E%7BT%7D%7D)
Let's substitute according to the formula.
![A= 50000(1+ \frac{10}{100}{)}^{5}](https://tex.z-dn.net/?f=A%3D%2050000%281%2B%20%5Cfrac%7B10%7D%7B100%7D%7B%29%7D%5E%7B5%7D)
<em>A=</em><em> </em><em>$80525.5</em>
Now, we can find the interest paid
![\large\boxed{I= A-P}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7BI%3D%20A-P%7D)
We'll have to deduct the total amount from the principal amount.
Let's substitute according to the formula.
![I= 80525.5-50000](https://tex.z-dn.net/?f=I%3D%2080525.5-50000)
<em>I=</em><em> </em><em>$30525.5</em>
<u>Hence</u><u>,</u><u> </u><u>the</u><u> </u><u>total</u><u> </u><u>amount</u><u> </u><u>paid</u><u> </u><u>after</u><u> </u><u>5</u><u> </u><u>years</u><u> </u><u>is</u><u> </u><u>$</u><u>80525.5</u><u> </u><u>and</u><u> </u><u>$</u><u>30525.5</u><u> </u><u>was</u><u> </u><u>paid</u><u> </u><u>as</u><u> </u><u>interest</u><u>.</u>
Answer:
x³ - (√2)x² + 49x - 49√2
Step-by-step explanation:
If one root is -7i, another root must be 7i. You can't just have one root with i. The other roos is √2, so there are 3 roots.
x = -7i is one root,
(x + 7i) = 0 is the factor
x = 7i is one root
(x - 7i) = 0 is the factor
x = √2 is one root
(x - √2) = 0 is the factor
So the factors are...
(x + 7i)(x - 7i)(x - √2) = 0
Multiply these out to find the polynomial...
(x + 7i)(x - 7i) = x² + 7i - 7i - 49i²
Which simplifies to
x² - 49i² since i² = -1 , we have
x² - 49(-1)
x² + 49
Now we have...
(x² + 49)(x - √2) = 0
Now foil this out...
x²(x) - x²(-√2) + 49(x) + 49(-√2) = 0
x³ + (√2)x² + 49x - 49√2